GROWTH PERFORMANCE OF ASIAN REDTAIL CATFISH (Hemibagrus nemurus) WITH DIFFERENT STOCKING DENSITY ON BOSTER SYSTEM - Putra Ali Syahbana Matondang; Usman M Tang; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on March 2019 until April 2019 held at UPT Fish Hatchery and Experimental Pond Fisheries and Marine Faculty Riau University. The aim of the research is to know the best stocking density on Asian redtail catfish (Hemibagrus nemurus) with boster system. The design of this research is an experimental model using Completely Randomized Design Factorial pattern (RAL) of 1 factor, 5 treatment levels, and 3 replications. The standard of treatment used is stocking density 400 individual/m3, 500 individual/m3, 600 individual/m3, 700 individual/m3, dan 800 individual/m3. During 42 days maintenance of the best treatment on stocking density 700 individual/m3 with an absolute weight growth was 4,41 g, the absolute length was 4,81 cm, the specific growth rate was 5,90%, feed efficiency was 91,68%, feed conversion ratio was 1,09, and survival rate was 91,66%. And the water quality during the research is the temperature was 25,9 to 27,1oC, pH was 6,9 to 7,2, dissolved oxygen was 6,0 to 6,8 mg/L and ammonia was 0,003 to 0,005 mg/L. Keyword :Hemibagrus nemurus,Stocking Density,Boster System